Comparison of pediatric injury patterns before and during the COVID-19 pandemic in Korea: a retrospective study - Geom Pil Nam; Woo Sung Choi; Jin-Seong Cho; Yong Su Lim; Jae-Hyug Woo; Jae Ho Jang; Jea Yeon Choi (Journal of Trauma and Injury)
Purpose The COVID-19 pandemic led to significant changes in the lifestyle patterns of children and affected the patterns of pediatric injuries. This study analyzed the changing patterns of pediatric injury overall and by age groups, based on the datasets before and during the COVID-19 pandemic. Methods This study is based on the data of patients who presented with injuries at 23 hospital emergency departments participating in the Emergency Department-based Injury In-depth Surveillance (EDIIS) conducted by the Korea Disease Control and Prevention Agency. The surveillance data was categorized by injury mechanism, location, activity, and severity. We analyzed the injury patterns of pediatric patients aged 0 to 15 years. Subgroup analysis was conducted by age group in children aged 7 to 15 years, 1 to 6 years, and <1 year. Results When comparing the COVID-19 pandemic period to the pre–COVID-19 period, the total number of pediatric patients with injuries decreased by 38.7%, while the proportions of in-home injuries (57.9% vs. 67.9%), and minor injuries (38.9% vs. 39.7%) increased. In the 7 to 15 years group, bicycle riding injuries (50.9% vs. 65.6%) and personal mobility device injuries (2.4% vs. 4.6%) increased. The 1 to 6 years group also showed an increase in bicycle accident injuries (15.8% vs. 22.4%). In the <1 year group, injuries from falls increased (44.5% vs. 49.9%). Self-harm injuries in the 7 to 15 years group also increased (1.6% vs. 2.8%). Conclusions During the COVID-19 pandemic period, the overall number of pediatric injuries decreased, while injuries occurring at home and during indoor activities increased. Traffic accidents involving bicycles and personal mobility devices and self-harm injuries increased in the 7 to 15 years group. In the <1 year group, the incidence of falls increased. Medical and societal preparedness is needed so that we might anticipate these changes in the patterns of pediatric injuries during future infectious disease pandemics.